Transient inverse analyses of overcoring data for improved stress estimation - Valley, Benoît (: ARMA, 2022)
Overcoring is a common technique for measuring stresses in mining projects. Knowledge of the in-situ stress state is essential to ensure the stability of underground infrastructures as well as to assess the induced microseismic risk associated with deep mining operations. There are different types of overcoring probes. Some are bonded in the pilot hole with an epoxy resin and allow for 3D stress measurement (e.g. CSIRO-HI), and others are based solely on a mechanical coupling of the probe, but are limited to biaxial stress measurement (e.g. USBM). The need to glue the probe to obtain a 3D measurement limits the applicability of this technique to short boreholes because it is technically difficult to glue probes in deep boreholes. In any case, traditionally the data analysis is done only based on the final deformation obtained after overcoring. In this paper we propose to use the transient deformation response during overcoring to: (1) allow to evaluate the 3D stress field from a single biaxial overcoring measurement, and (2) add a quality control component by reproducing the entire overcoring response. The general principle of our approach is to simulate the transient response of overcoring by numerical elastic simulation. The principle of superposition is used to derive the responses for any set of parameters from a limited number of basic models and thus allows to limit the total number of model runs. Such approach allows for a systematic inversion procedure to be applied for determining the optimal parameter sets that best capture the transient response of the overcoring. This allows the estimation of a 3D stress tensor from biaxial measurements. It also allows to have a quality control on the measurements evaluating the quality of the fit between the model and the data. In this paper, we evaluate the robustness of the proposed approach by performing a systematic sensitivity analysis on the stress estimation from the inversion of transient overcoring data. We demonstrate the advantages of the approach but also its limitations. The preliminary results obtained in this study suggest that the transient overcoring response contains sufficient information for constraining efficiently the 3D stress tensor. The inversion must be performed using multiple starting point, and the mode of the obtained calibrated parameters is in close adequacy with expected values, while some outliers can be present in the calibrated set. Further work is required for confirming these encouraging results by testing of broader range of stress configurations and applying the method to actual field measurements.
, 2022